2007
DOI: 10.1021/jp067136p
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Electronic and Vibrational Structure of the 1-Ethyl-3-methylimidazolium Bis(trifluoromethylsulfonyl)amide Room-Temperature Ionic Liquid Surface:  A Study with XPS, UPS, MIES, and HREELS

Abstract: The near-surface structure of the room-temperature ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)amide has been investigated as a function of temperature between 100 and 620 K. We used a combination of photoelectron spectroscopies (XPS and UPS), metastable induced electron spectroscopy (MIES), and high-resolution electron energy loss spectroscopy (HREELS). The valence band and HREELS spectra are interpreted on the basis of density functional theory (DFT) calculations. At room temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(118 citation statements)
references
References 30 publications
9
107
0
Order By: Relevance
“…27,34,35 On the other hand, IL surfaces under vacuum that contain aliphatic alkyl chains longer than ethyl (i.e., butyl or longer) tend to be populated with nonpolar carbon chains, whereas the ionic parts of the charged imidazolium ring or the anion tend to stay in the bulk polar liquid phase. [42][43][44] Additionally, the population of alkyl chains in the near-surface region decreases with an increase of anion size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27,34,35 On the other hand, IL surfaces under vacuum that contain aliphatic alkyl chains longer than ethyl (i.e., butyl or longer) tend to be populated with nonpolar carbon chains, whereas the ionic parts of the charged imidazolium ring or the anion tend to stay in the bulk polar liquid phase. [42][43][44] Additionally, the population of alkyl chains in the near-surface region decreases with an increase of anion size.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, both experimental and theoretical investigations have recently found that the IL surface composition may be more or less populated with alkyl and/or fluorinated moieties depending on the type of anion and cation substituents. [27][28][29][30][31][32][33][34][35] However, the experimental conditions (distance between the metal target and liquid surface, gas pressure, current and time, and voltage change) used thus far have varied from one study to another, making it almost impossible to compare and correlate the influence of these parameters. 11,[22][23][24][25][26] Nonetheless, it is apparent that the size of NPs depends on the type of IL and on the discharge current.…”
Section: Introductionmentioning
confidence: 99%
“…It was verified by MIES and UPS that, as far as the electronic structure of the films prepared on Ag is concerned, their properties are identical with those prepared by similar procedures on Au. 16,19,20 The RAIRS setup contained a Bruker IFS 66v/S vacuum Fourier transform infrared spectrometer, connected directly to a UHV chamber. The Mid-IR beam was coupled to the UHV system through KBr optics, and focussed under an angle of 83.5 degs to the surface normal onto the silver substrate.…”
Section: Methodsmentioning
confidence: 99%
“…The results were later interpreted by us on the basis of DFT calculations on isolated ion pairs. 19,20 While these studies delivered considerable insight into the structure of the surface-near region at room temperature (RT), the change in the structure of the films during the liquid-toamorphous solid phase transition, which takes place during fast cooling, remained poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…[ 54 ] It should be kept in mind, however, that most surface science studies on IL interfaces have been performed on ex-situ prepared fi lms so far. In spite of the novelty of the fi eld, a broad spectrum of experimental methods have already been applied to IL fi lms, among which are X-ray photoelectron spectroscopy (XPS), [ 32-39 , 44 , 46-50 , 56 , 57 , 70 ] ultraviolet photoelectron spectroscopy (UPS), [ 33 , 35 , 40-42 , 70 ] infrared refl ection absorption spectroscopy (IRAS), [52][53][54][55] inverse photoelectron spectroscopy (IPES), [ 41 , 42 , 70 ] near edge X-ray absorption fi ne structure (NEXAFS), [ 41 ] metastable ion photoelectron spectroscopy (MIES), [33][34][35] direct recoil spectroscopy (DRS), [ 30 , 31 ] high-resolution electron energy loss spectroscopy (HREELS), [ 34 ] low energy ion scattering (LEIS), [ 32 ] time-of-fl ight secondary ion mass spectrometry (TOF-SIMS), [ 37 ] soft X-ray emission spectroscopy (SXES), [ 70 ] and Rutherford backscattering spectroscopy (RBS). [ 71 ] The number of studies is yet rather limited, however.…”
Section: Progress Reportmentioning
confidence: 99%